2007
DOI: 10.1111/j.1365-2036.2007.03562.x
|View full text |Cite
|
Sign up to set email alerts
|

Review article: the role of butyrate on colonic function

Abstract: SUMMARY BackgroundButyrate, a short-chain fatty acid, is a main end-product of intestinal microbial fermentation of mainly dietary fibre. Butyrate is an important energy source for intestinal epithelial cells and plays a role in the maintenance of colonic homeostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

41
1,612
5
41

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 2,221 publications
(1,784 citation statements)
references
References 210 publications
41
1,612
5
41
Order By: Relevance
“…Several studies showed that butyrate functions as a HDI, reduces proliferation and induces apoptosis as well as differentiation. Butyrate regulates the expression of genes and proteins involved in cell cycle control like p21 and Cyclin D1, leading to a cell cycle arrest in human colon cancer cells (Hamer et al 2008;Hinnebusch et al 2002;Siavoshian et al 2000). Lately, Hu et al (2011) as well as Humphreys et al (2013) showed that butyrate also influences miRNA expression in HCT116 and HT29 colon cancer cells, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed that butyrate functions as a HDI, reduces proliferation and induces apoptosis as well as differentiation. Butyrate regulates the expression of genes and proteins involved in cell cycle control like p21 and Cyclin D1, leading to a cell cycle arrest in human colon cancer cells (Hamer et al 2008;Hinnebusch et al 2002;Siavoshian et al 2000). Lately, Hu et al (2011) as well as Humphreys et al (2013) showed that butyrate also influences miRNA expression in HCT116 and HT29 colon cancer cells, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…SCFAs increase cell metabolism by more than 80% and the production and secretion of mucins by the colon epithelium more than twentyfold 8,33 . Experimental models that inhibit the oxidation of SCFAs or that use animals that have been silenced for the MUC-2 gene are capable of causing inflammation of the colon mucosa to appear, with histological similarities to diversion colitis 10,27,37,34 . All these points reinforce the important role played by SCFAs in relation to the capacity of the colon epithelium to produce mucins and consequently to protect the mucosa against aggression coming from the intestinal lumen 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Reductions in the supply of SCFAs, as occurs during intestinal diversion operations, are accompanied by morphological and functional changes, thereby causing reductions in protein synthesis capacity 26 . The mechanisms through which shortages of SCFAs lead to lower capacity for mucin production are still not completely clear 9,27 . Studies have shown that intestinal diversion reduces the quantities of dietary fiber and modifies the bacterial populations in the segment excluded and it decreases the production of SCFAs, thereby causing a state of nutritional deficiency for the cells of the colon mucosa [28][29][30] .…”
Section: Discussionmentioning
confidence: 99%
“…Members of E. rectale, Roseburia, and R. bromii are main producers of butyrate in the colon (71,107,109). It has been shown that increasing butyrate-producing bacteria and butyrate production is closely linked with prevention of the progression from steatosis to hepatocarcinogenesis and improving hepatic inflammatory and oxidative stress indexes and gut integrity (74,110,111). This would appear to indicate that there is a mutualistic relation between the gut microbiota and the host; dietary ingredients such as RS could induce special species of bacteria that produce metabolic products such as butyrate.…”
Section: Introductionmentioning
confidence: 99%
“…Akkermansia municiphila has been known as a major propionate-producing bacterium (70) and Eubacterium hallii, Eubacterium rectale, Roseburia inulinivorans, Faecalibacterium prausnitzii, Clostridium lavalense, Bacteroides uniformis, and Ruminococcus bromii appear to be responsible for most of butyrate production (70)(71)(72). Butyrate and propionate at low amounts exert multiple advantageous effects on the host, including the prevention of colonic carcinogenesis, inflammation, and oxidative stress; improvement in intestinal barrier function; and stimulation of satiety and lipid oxidation in hepatocytes (73,74). Acetate may be more important for modulating insulin sensitivity and metabolic disease (75) and the development of diabetes (76).…”
Section: Introductionmentioning
confidence: 99%